Chemical composition and toxicity of effluents from unhairing baths: case study of the Batna Unit, Algeria - Selma, Benbrahim; Sabrina, Tamersit; Afaf, Lalmi; Chahrazad, Amrane; Fatima, Chemlal (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/Purpose: The leather industry in Algeria contributes significantly to the economy, but its unhairing process generates highly polluted wastewater. This study aimed to characterize the chemical composition of unhairing bath effluents and assess their environmental toxicity. Methods: The study focused on wastewater samples from the Batna tannery unit, where sheep and goat skins were processed. Thirteen samples were collected manually over 35 days (April 5–May 10, 2022), and standard chemical analyses were conducted to evaluate parameters such as pH, conductivity, total suspended solids (TSS), sulfides, ammonia ions, and proteins. Results: The results showed that the wastewater had a high pH (12.47 on average), high conductivity (13.38 mS/cm), and significant levels of pollutants: sulfides (1120–1650 mg/L), TSS (862–2220 mg/L), and chemical oxygen demand (10.422–43.747 mg/L). Additionally, the wastewater contained free amino acids and proteins, products of partially hydrolyzed skin proteins, increasing its toxicity. Conclusions:The study highlighted the severe environmental risks of untreated unhairing wastewater, underscoring the need for effective treatment solutions to mitigate pollution. The findings provide important insights into the environmental challenges of the leather industry and stress the importance of sustainable wastewater management.